Hubungan Pola Makan Dan Konsumsi Kopi Dengan Kejadian Gastritis Pada Lansia Di Kelurahan Manisrejo Kecamatan Taman Kota Madiun - Desti Maharani; Pipid Ari Wibowo; Hanifah Ardian (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2020)
Background: The number of gastritis sufferers increases annually was estimated about 1.8-2.1 million from the population, even in the old age of gastritis becoming a frequent disease because of complications. According to data obtained by the genesis number of gastritis over manisrejo also showed 48.7%. To prevent and overcome the increase in cases of gastritis, people, governments, and other private health sectors need to know about risk factors that can affect the onset of the disease. The purpose of this study was to determine the associated of diet and coffee consumption to the incidence of gastritis on elderly people in Manisrejo Taman sub-district of Madiun. The method: The kind of this research was analytic observational used of cross sectional study. The population of this study were all over the Manisrejo elderly of medical care in the Banjarejo Health Center chosen by research criteria. The number of samples needed was142 samples by the sampling technique of this research was simple random sampling used Chi-Square analysis. The results: Based on bivariate analysis,diets variable p = 0,003(RP= RP=2,035; 95% CI 1,403-2,953) and coffee consumption variable p = 0,007 (RP=0,541; 95% CI 0,368-0,795)were associated to the incidence of gastritis on elderly people in Manisrejo Taman sub-district of Madiun. Conclusion: A very large variable has an effect on the diet of gastritis, while the one with the least risk to the occurrence of gastritis is a coffee consumption. Increased information about prevention of gastritis risk factors and the monitoring of gastritis evaluation is required. Public response has been made to the prevention efforts of various risk factors known as gastritis. Keywords: gastritis, the diets, coffee consumption